Islamic Perspective Marketing Communication Strategy - Astri Dwi Andriani (Indonesian Journal of Advanced Research, 2023)
Islam in Indonesia is the largest majority of Muslims in the world. Of course this is a great opportunity for Muslim entrepreneurs to sell their products. One of the efforts that can be made by Muslim entrepreneurs in introducing their products is through Islamic-based marketing communications. This study aims to determine marketing communication strategies from an Islamic perspective. This type of research uses library research with content analysis techniques, data collection used is observation, documentation method. The results of the study state that if I follow the example of the Prophet when trading, then Muslim entrepreneurs must prioritize trade ethics and ethics based on Islamic values.